Regional Inequalities in Brazil: Divergent Readings on Their Origin and Public Policy Design - Simone Affonso da Silva (EchoGéo)
This article presents divergent readings on the origin of regional inequalities in Brazil by four scholars: Celso Furtado, Wilson Cano, Francisco de Oliveira, and Ruy Moreira. Moreover, it discusses the essence of major policies established by the Brazilian Federal Government since the mid-20th century in order to politically, economically, and socially impact the sociospatial dynamics that are at the core of the regional issue. In this sense, Development Poles, National Integration and Development Axes, and the National Policy for Regional Development stand out. Each reading and intervention proposal for the regional problematic has its own set of underlying ideologies and political projects, which may have a higher or lower degree of adherence to the purposes of hegemonic players in power, or that are appropriated by them. Therefore, elucidating the essence and the consequences of those divergent readings and proposed actions regarding the regional problematic is vital in order to understand the role of regional inequalities in Brazil's socioeconomic development landscape.